Aplikasi Media Pembelajaran Interaktif Bagi Santri TPA Berbasis Android - Nuning Melianingsih; Harjono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
The rapid development of technology has changed many facets of human life. One example of the changing side of life due to the development of information technology is children's interest in learning, especially in learning Islam. Efforts that can be made to restore the interest in learning the religion of Islam is by making Android applications a fun and educative learning media for TPA students. The steps taken to create an android application are analysis of needs and material collection, designing images, designing animations, creating applications using Adobe Flash Professional CS6, testing applications and applications. Based on the results of the study by testing and filling out the questionnaire, respondents agreed that the smartphone they owned was used as a fun and educative learning media, did not make them bored quickly and the respondents agreed if they could learn while playing.